Bidirectional AC/AC converter linking two microgrids in a flexible microgrid - Vinh, Nguyen The; Dung, Nguyen Van (Institute of Advanced Engineering and Science, 2025)
The proposed single-phase flexible AC/AC converter in an AC microgrid controlled by the PWM method is presented and tested with a small capacity. This converter uses a simple and small number of semiconductor switches and passive elements to limit power loss and increase efficiency. It has higher reliability, safety, and continuity of power supply in operation than traditional AC/AC converters due to the power circuit structure of the converter. It has the function of increasing or decreasing voltage when connecting to two microgrids and can be directly connected to distributed energy sources in microgrid systems with distributed power sources and loads. Besides, the AC/AC converter can be connected to the storage system to improve continuity and voltage stability for the grid. The performance of the proposed converter is compared with existing similar converters. The paper presents the analysis of simulation results by OrCAD with power values from 0.1-5 kW and experimental power with typical values in the range of 0.5-3.5 kW at different scenarios of the converter.